Determinants of Financial Stability in Nepalese Commercial Banks: An Empirical Analysis of Internal and External Factors - Shiva Raj Ghimire; Nirdosh Kumar Agarwal; Ashok Basnet (Interdisciplinary Journal of Management and Social Sciences, 2025)
This study explores the determinants of financial stability in Nepalese commercial banks by analyzing data from 20 banks over an 11-year period (2013–2023). The research investigates the impact of both internal factors, such as bank size, profitability, capital, and loan loss provisions, and external factors, including market concentration, GDP growth, inflation, and exchange rates. Data were obtained from secondary sources, including annual reports, NRB economic surveys, and publications. Descriptive statistics, correlation, and regression analyses are employed to examine the relationships between internal and external factors and financial stability. The Z-score is used as the dependent variable to measure bank stability. The study finds that internal factors such as bank size, capital adequacy, and loan loss provisions significantly influence the financial stability of Nepalese commercial banks. Bank size negatively affects stability, while capital and LLP have a positive impact. Other external variables, such as concentration in the market, growth in the GDP, and inflation are also significant although they are less coherent and non-significant in combination models. The study concludes that those internal variables, especially size and risk management practices plays a greater role within deciding bank stability in Nepal as compared to the external macroeconomic factors. The findings point out that profitability is not a key determinant but sound provisioning and capitalization makes a company resilient. The above evidence indicates that the policies must focus on enhancing internal bank activities in order to ensure stability. The paper suggests that policy makers need to enhance the regulatory control of the big banks and encourage good risk management practices internally. Internal influences are more direct as compared to external economic influences and it is advisable that banks should increase the provisioning of loans to increase their stability.